Involvement of Kynurenine Metabolism in Bipolar Disorder: An Updated Review - Zhang, Peifen; Huang, Huimin; Gao, Xingle; Jiang, Jiajun; Xi, Caixi; Wu, Lingling; Fu, Yaoyang; Lai, Jianbo; Hu, Shaohua (Frontiers in Psychiatry, 2021)
Bipolar disorder (BD) is a severe affective disorder, mainly characterized by alternative depressive and manic or hypomanic episodes, yet the pathogenesis of BD has not been fully elucidated. Recent researches have implicated the altered kynurenine (KYN) metabolism involved in the neurobiology of BD. Excessive activation of the immune system is observed in patients with BD and it further accelerates the KYN pathway metabolism. Changes of the KYN metabolites have effects on neuronal receptors and are involved in neuroendocrine transmissions. Various alterations of the KYN metabolites in distinct tissues, such as cerebrospinal fluid, brain, as well as peripheral circulatory system in BD, are associated with mood, psychotic symptoms, and cognitive functions. Interactions between KYN metabolism and the immune system may contribute to the neuropathogenesis of BD. In this review, we briefly introduce the KYN pathway and describe the immune dysregulation in BD as well as their interactions. We then focus on the research advances on the KYN metabolism in BD, which holds promise for novel treatment targets in patients stricken with this disorder.